IMPLEMENTASI METODE ECONOMIC ORDER QUANTITY PADA APLIKASI PENGENDALIAN BAHAN PRODUKSI SANDAL MIRADO - Guntara, Dwiky; Nasution, M. Irwan Padli; Nasution, Adnan Buyung (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Mirado slipper home industry is a company that controls production materials such as alaska, lower thread, wedding nails, leather layers, Japanese glue, PU glue, latex glue, slipper box, tissue and sandals. This inventory system performs procurement of goods which results in a buildup of raw materials. Every time you order material, the production of mirado sandals keeps ordering, but it is not yet effective and efficient. Researchers conduct research to minimize the supply of economical supplies, so as to increase operational activities. The data needed in this study, used direct data collection techniques, namely, observation, interviews and literature studies. This application uses the PHP Hypertext Preprocessor programming language, MySQL as a database, Xampp as a web server. To control these production materials, researchers here use the EOQ (Economic Order Quantity) method, which is to find out the number of purchases of production materials, the total cost of production inventory, the frequency of ordering production materials and to know the point of reordering, in the form of a web application. With the development of this application, effective and efficient results are obtained in minimizing the supply of production materials.